COMPETITIVENESS OF INDONESIA'S CREATIVE ECONOMY INDUSTRY IN THE GLOBAL MARKET: SCP APPROACH - Wiwin indrayanti; Febriana Khoirun Nisa; Dio Caisar Darma; Arkanudin Rizki Permono (Universitas Negeri Semarang, 2026)
Indonesia's creative economy industry has occupied a strategic position as a major contributor to the national economy, with its contribution to Gross Domestic Product steadily increasing over the past decade. This study aims to analyze the competitiveness of Indonesia's creative economy industry in the global market using the Structure-Conduct-Performance (SCP) approach. The SCP framework was chosen because it allows for a comprehensive analysis of market structure characteristics, industry player behavior, and resulting performance achievements. The method used is a descriptive qualitative method based on a systematic literature study by searching sources from Google Scholar, Scopus, and ScienceDirect for the period 2018 to 2026. The results show that the industry's competitiveness is influenced not only by market structure but also by the ability of entrepreneurs to innovate, utilize digital technology, and create products with unique and strong identities. These factors are the main drivers of increased competitiveness amidst increasingly dynamic global competition.Therefore, the government needs to strengthen its role as a facilitator by providing a conducive business climate, simplifying regulations, and increasing business access to global markets. Furthermore, it is necessary to develop creative economy centers in various regions that are connected to local potential and international market needs. As a policymaker, the government needs to expand collaboration with the private sector, universities, and creative communities to strengthen the industry ecosystem. With the support of targeted policies and synergy between stakeholders, the creative industry has a significant opportunity to increase competitiveness and become a leading sector in driving national economic growth in the future.